Mobile-phone-based colourimetric analysis for determining nitrite content in water - Chanida Puangpila (2018)
© 2018 CSIRO. A cost-effective and portable colourimetric analyser installed on a mobile phone was used to measure nitrite in water samples in Chiang Mai City, Thailand. The colourimetric detection was based on the Griess reaction, in which nitrite ion reacts with sulfanilic acid under acidic conditions to produce a diazonium salt that further reacts with N-(1-naphthyl)-ethylenediamine dihydrochloride to form a red-violet azo dye. Under controlled conditions using a light-tight box with LED flash lights, images of the red-violet solution were captured using a built-in camera and further analysed by a program, Panalysis, on the mobile phone. The calibration graph was created by measuring the red colour intensity of a series of standard nitrite solutions from 0.09-1.8 mg N L-1. The calibration equation was then automatically stored for nitrite analysis. The results demonstrated good performance of the mobile phone analyser as an analytical instrument. The accuracy (RE <4%) and precision (RSD ≤ 1%, intra- and inter-day) were also obtained with a detection limit of 0.03 mg N L-1 and a sample throughput of 40 samples per hour. Our results establish this simple, inexpensive and portable device as a reliable in-field monitor of nitrite in environmental waters.